The Procedural Syllabus and the Task Syllabus: How Similar, How Different? - Sasan Baleghizadeh (Asociación Colombiana de Profesores de Ingles, 2015)
The present paper aims to convince readers that the terms procedural and task syllabuses, often used interchangeably and synonymously, are fundamentally different from each other. After reviewing the underlying principles of these two syllabuses, it is contended that they both view pedagogic tasks as the point of departure in designing second/foreign language courses. Besides, neither of them is built on any pre-specified linguistic units such as structures, functions, notions, etc. In spite of this striking similarity, it is argued that these two syllabus types differ from each other in terms of task selection, task gradation, task implementation, and input characteristics.